2017
DOI: 10.1038/s41467-017-00930-9
|View full text |Cite
|
Sign up to set email alerts
|

NMI and IFP35 serve as proinflammatory DAMPs during cellular infection and injury

Abstract: Damage-associated molecular patterns (DAMP) trigger innate immune response and exacerbate inflammation to combat infection and cellular damage. Identifying DAMPs and revealing their functions are thus of crucial importance. Here we report that two molecules, N-myc and STAT interactor (NMI) and interferon-induced protein 35 (IFP35) act as DAMPs and are released by activated macrophages during lipopolysaccharide-induced septic shock or acetaminophen-induced liver injury. We show that extracellular NMI and IFP35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 48 publications
1
86
1
Order By: Relevance
“…report that upregulation of NMI correlated with inflammatory signature in the patients with congenital erythrocyte aplasia . Serum NMI is also found to be correlated to the severity of inflammation and mortality of patients with sepsis . HBV‐ACLF syndrome has some similarities to sepsis, suggesting that NMI may also involve in the progression of HBV‐ACLF.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…report that upregulation of NMI correlated with inflammatory signature in the patients with congenital erythrocyte aplasia . Serum NMI is also found to be correlated to the severity of inflammation and mortality of patients with sepsis . HBV‐ACLF syndrome has some similarities to sepsis, suggesting that NMI may also involve in the progression of HBV‐ACLF.…”
Section: Discussionmentioning
confidence: 91%
“…NMI is also involved in antiviral response against viral infections . Recently, it is demonstrated that NMI correlates with the severity of inflammation in sepsis patients . The severity of ACLF is also correlated with inflammation, which is contributing to prognosis of ACLF .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations